1992
DOI: 10.1149/1.2221272
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Enhanced Chemical Vapor Deposition of Silicon Dioxide Films Using Tetraethoxysilane and Oxygen: Characterization and Properties of Films

Abstract: SiO2 films were deposited in a commercial single wafer parallel plate plasma deposition reactor using tetraethoxysilane as the silicon source. Deposition conditions were varied to produce films with widely differing properties. Electrical, optical, mechanical, and wet-etch-rate characterization were then used to investigate the as-deposited film quality. Moisture uptake was also measured and related to the initial properties. The films were studied in an ongoing investigation of silicon dioxide interlevel diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 2 publications
0
30
0
2
Order By: Relevance
“…From the leakage current measurement data, it is found that the average breakdown E-field is very much thickness dependence and can be calculated from Fig. [23][24][25] Apart from above results, the ALD film had a much smoother surface morphology than conventional PECVD films owing to the selflimiting nature of ALD reaction mechanism. Hence, ALD grown SiO 2 film with 100 cycles exhibits higher breakdown E-fields.…”
Section: Electrical Breakdown Strength Of Ald Grown Sio 2 Gate Diementioning
confidence: 85%
“…From the leakage current measurement data, it is found that the average breakdown E-field is very much thickness dependence and can be calculated from Fig. [23][24][25] Apart from above results, the ALD film had a much smoother surface morphology than conventional PECVD films owing to the selflimiting nature of ALD reaction mechanism. Hence, ALD grown SiO 2 film with 100 cycles exhibits higher breakdown E-fields.…”
Section: Electrical Breakdown Strength Of Ald Grown Sio 2 Gate Diementioning
confidence: 85%
“…[1][2][3][4] SiO 2 films can be deposited by evaporation, sputtering, sol-gel, chemical vapor deposition, and other methods. [1][2][3][4] SiO 2 films can be deposited by evaporation, sputtering, sol-gel, chemical vapor deposition, and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…51 The slight reduction in dielectric constant at higher deposition temperatures may be attributed to the reduction in Si-OH bonds (as indicated by the FTIR results discussed earlier), which are characteristically more polarizable and have been reported to be the cause of higher dielectric constants. 52,53 The electrical resistivities of the samples, shown in Figure 7, were taken from low field (<0.1 MV cm À1 ) I-V measurements of the $50 nm and $1000 nm thick samples. The resistivities of both types of samples are on the order of 10 15 Xcm when deposited at 100 C, but increase with deposition temperature to a resistivity on the order of high 10 16 to low 10 17 Xcm at both 250 C and 400 C. Qualitatively, the trend compares with the optical band gap discussed earlier, in that the gap rather significantly changes between the 100 C and 250 C deposition temperatures, and changes less between 250 C and 400 C. The similarity in the jump in characteristics from 100 C to 250 C suggest that a temperature between these is required to promote adequate hydrogen diffusion to enhance hydrogen bond-breaking and increase structural arrangement, as is also observed in the growth of Si.…”
Section: E Electrical Propertiesmentioning
confidence: 99%